A high performance polybenzoxazine via smart ortho-norbornene functional benzoxazine monomer based on ring-opening metathesis polymerization. (June 2019) - Zhang, Kan; Liu, Yuqi; Wang, Yuting; Sun, Lin
Monofunctional benzoxazine with ortho -norbornene functionality ( o HPNI-a) has been synthesized via Mannich condensation. The benzoxazine monomer containing norbornene group can be polymerized by ring-opening metathesis polymerization (ROMP) to form a side-chain benzoxazine functionalized polynorbornene (poly( o HPNI-a)side ) with number-average molecular weight 3840 and weight-average molecular weight 7290. The structures of synthesized monomer and side-chain functionalized linear polymer have been confirmed by 1 H nuclear magnetic resonance spectroscopy and Fourier transform infrared (FTIR) spectroscopy. The further thermal curing polymerization mechanisms of poly( o HPNI-a)side are monitored by in situ FTIR and differential scanning calorimetry (DSC). Activation energy of polymerization for poly( o HPNI-a)side is also studied by DSC. The polybenzoxazine obtained by ROMP and further thermally activated ring-opening polymerization exhibits much higher thermal stability than the polybenzoxazine directly formed by traditional thermal curing.